2016
DOI: 10.18016/ksujns.98227
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins in Poultry Nutrition

Abstract: ABSTRACT:Aflatoxin is generated by mycotocins and it is causes a big losses and rasied the managament costs that's becuase of its extremely high toxicity on unit basis. Research during the last five decades has explored the negative effects of the aflatoxins on health of poultry and sometimes caused disease called Aflatoxciosis. They clamid it has bad effects in both broilers and layers. For example in broilers it is effects on immunity system, performance and gastro intestinal tract and in layers it is caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…AFB 1 also affect laying hens; losses are pronounced regarding reduced egg production and egg quality as a result of contamination with aflatoxin residues in eggs and muscles. Feed to egg AFB 1 transmission ratio is approximately 5 000:1 [74]. A substantial percentage of the egg samples (28%) showed AFB 1 levels (0.79 ± 0.45 μg kg −1 ) in commercial eggs [77].…”
Section: Effects On Poultrymentioning
confidence: 98%
See 1 more Smart Citation
“…AFB 1 also affect laying hens; losses are pronounced regarding reduced egg production and egg quality as a result of contamination with aflatoxin residues in eggs and muscles. Feed to egg AFB 1 transmission ratio is approximately 5 000:1 [74]. A substantial percentage of the egg samples (28%) showed AFB 1 levels (0.79 ± 0.45 μg kg −1 ) in commercial eggs [77].…”
Section: Effects On Poultrymentioning
confidence: 98%
“…Hussain et al reported experimental birds intoxicated with 400-800 μg kg −1 AFB 1 showed depression, ruffled feathers, watery feces, decrease in water and feed consumption, and nervous signs as torticollis and mortality [71]. Trebak et al reported listlessness, anorexia [72]; other symptoms include poor feed utilization, stunted growth, decrease weight gain [73,74]; reduced egg weight and production. High levels of aflatoxins in broilers and turkeys cause hepatomegaly, fatty degeneration, fatty liver, bile conduct proliferation, periportal fibrosis, renal petechiations, tubular nephrosis, interstitial nephritis, and splenic atrophy [67,75].…”
Section: Effects On Poultrymentioning
confidence: 99%
“…Even with the fast absorption, aflatoxin B1 showed detrimental effects on the gut epithelia in broilers, increasing gut permeability, reducing apparent ileal digestible energy, and reducing standardized nitrogen and amino acids digestibility [90]. When broilers were fed with AFB1 contamined diets, birds showed a reduction in the intestinal density [91]. Diet with 1 mg AFB1/kg for 4 weeks promoted necrosis in the crop, and catarrhal enteritis with lymphocytic or mononuclear cell infiltrations in the intestine of chickens [84].…”
Section: Mycotoxinsmentioning
confidence: 99%
“…Pada ayam pedaging, aflatoksin B1 akan mempengaruhi pada sistem imun, pertumbuhan dan saluran pencernaan, sedangkan pada ayam petelur menurunkan produksi telur dan daya tetas (Alhousein & Gurbuz 2015). Tantangan terbesar mikotoksikosis pada unggas adalah gejala klinis bersifat non-spesifik sehingga sangat menyulitkan diagnosis dan masalah dalam mengambil tindakan yang tepat.…”
Section: Dampak Mikotoksin Pada Kesehatan Ternakunclassified
“…Rocha et al (2014) menyatakan bahwa mikotosin merupakan zat yang bersifat karsinogenik. Aflatoksin memiliki sifat onkogenik dan imunosupresif, serta akan menginduksi infeksi pada manusia yang terkontaminasi zat ini (Alhousein & Gurbuz 2015). Sifat ini berkontribusi secara signifikan dalam meningkatkan risiko kanker hati (hepato-carcinogenic) pada manusia, terutama hubungannya dengan infeksi virus hepatitis B (VHB) kronis Wild & Gong 2009).…”
Section: Dampak Mikotoksin Pada Kesehatan Manusiaunclassified